Unified Constructions of the Regular Heptagon and Triskaidecagon - Ruhland, Helmut (Computer Tools in Education, 2025)
Constructions of regular heptagon and triskaidecagon by trisection of an angle are well known. An elegant construction of the heptagon by S. Adlaj shows a 3-fold symmetry related to a Galois group. Based on the latter construction, in this article one more for the heptagon and two more for the triskaidecagon are presented, all using angle trisection.